2020
DOI: 10.3389/fpsyg.2020.00903
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Correlates of Reading Fluency in Chinese School-Aged Children

Abstract: Previous studies have showed that reading fluency is strongly associated with cognitive skills, including rapid automatized naming, phonological awareness, orthographical awareness, and so on. However, these studies are largely based on alphabetic languages, and it remains unclear which cognitive factors contribute to the development of reading fluency in logographic Chinese, a language in which the graphic forms map onto morphemes (meaning) rather than phonemes. In Study 1, we tested 179 Chinese children aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Previous studies that investigated the cognitive dynamics underlying reading fluency also revealed substantial contribution of PA to word (Landerl et al, 2019) and text reading fluency (Georgiou et al, 2008). In a non-alphabetic writing system such as Chinese, the strong links between PA and character recognition (Ho and Bryant, 1997;Li et al, 2012;Liu et al, 2017) and sentence reading fluency (Lei et al, 2011;Xue et al, 2013;Bai et al, 2020) have also been confirmed although characteristics of Chinese scripts make the grapheme-phoneme mapping different from that of an alphabetic writing system.…”
Section: Contribution Of Phonological Awareness (Pa) To Reading In Children With Nh and Hlmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous studies that investigated the cognitive dynamics underlying reading fluency also revealed substantial contribution of PA to word (Landerl et al, 2019) and text reading fluency (Georgiou et al, 2008). In a non-alphabetic writing system such as Chinese, the strong links between PA and character recognition (Ho and Bryant, 1997;Li et al, 2012;Liu et al, 2017) and sentence reading fluency (Lei et al, 2011;Xue et al, 2013;Bai et al, 2020) have also been confirmed although characteristics of Chinese scripts make the grapheme-phoneme mapping different from that of an alphabetic writing system.…”
Section: Contribution Of Phonological Awareness (Pa) To Reading In Children With Nh and Hlmentioning
confidence: 87%
“…In addition to PA, OK which refers to the ability to use visualorthographic information during processing printed words (Barker et al, 1992;Rakhlin et al, 2014) is closely related to reading in alphabetic and non-alphabetic writing systems (O'Brien et al, 2011;Elhassan et al, 2017;Bai et al, 2020). In an alphabetic writing system, learning to read begins with learning the alphabetic principle by associating letters with their names and sounds (Shmidman and Ehri, 2010).…”
Section: Contribution Of Orthographic Knowledge (Ok) To Reading In Children With Nh and Hlmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, phonological processing has been revealed to significantly classify individuals with and without dyslexia (Wang & Bi, 2021). Thus, the before-mentioned inconsistency can be most likely explained by the multiple deficit model (Pennington, 2006(Pennington, , 2012, which proposes that a specific single deficit cannot explain all cases of dyslexia, and explained by the developmental perspective, which indicates that the effect of a particular cognitive skill on reading acquisition is a function of the developmental stage (Bai et al, 2020;Ferrer et al, 2007). Since multiple factors and cognitive-linguistic skills work together in reading development, deficits of any component may lead to reading problems.…”
Section: The Speech Processing Related Left Tpc and Readingmentioning
confidence: 99%
“…Individuals of normal intelligence with TSC might be described by their parents as having academic difficulties in school performance. The TSC-associated neuropsychiatric disorders (TAND) checklist was developed (Bai et al, 2020), and the data collected through the checklist showed that 60.5% of TSC patients aged <18 years and 54.8% aged >18 years had certain degrees of academic difficulty (de Vries et al, 2018a). It can be seen that even if there is no systematic evaluation to confirm the relationship between TSC and academic difficulties.…”
Section: Introductionmentioning
confidence: 99%